Gestión ambiental en el sector público de Costa Rica: indicadores de referencia para aspectos ambientales comunes (UNED Research Journal, 2014)
Environmental management in the Costa Rican public sector: baseline indicators for common environmental aspects. Since 2011 the Costa Rican public sector has been mandated to develop environmental management programs for the reduction of negative environmental impacts (MINAE-S Executive Decree 36499). Some environmental aspects are common to most institutions: water, paper, electricity and fuel consumption, and generation of Greenhouse Gases (GHG). Here I present common environmental indicators to serve as a baseline to assess effectiveness in the sector over time. I analyzed consumption records delivered by the institutions to the Ministry of Environment and Energy. I found the following consumption indicators: a) 2,76m3 of water/employee/month; (b) 411,5 sheets/employee/month; (c) 206,78kWh/employee/month; (d) 8,03kWh/m2 month; (e) 20,29L of fuel per employee/month. For the generation of carbon dioxide equivalent, the following estimates were used: 17,04kg of CO2e/employee/month for electrical energy consumption; (b) 53,07kg of CO2e/employee/month for consumption of fuel by transport vehicles. No significant differences were found between the ministries and decentralized public institutional sector; with the exception of the consumption of electricity by area (Test t-student; t=-2,731; p=0,009), where the highest value was observed in the decentralized public institutional sector (11,06kWh/m2/month). This results represent the starting point for future studies to analyze the effectiveness of environmental management in the Costa Rican public sector.
Keywords: Environmental management; Costa Rican public sector; public institutions; institutional environmental management programs; MINAE Executive Decree No. 36499; environmental indicators.